The distribution and expression of the nitric oxide system during renal ageing and the effect of sex steroid modulation - Clifford, Bethan L. (2016)
The protective effect of female sex in renal ageing and cardiovascular function is widely accepted, but poorly understood. Previous evidence has suggested a role for the nitric oxide and renin-angiotensin systems, though the precise mechanisms by which they elicit these effects remain elusive. Female animals and humans have increased nitric oxide bioavailability with age in comparison to males, and this effect can be negated by ovariectomy surgery, suggesting an interaction between ovarian steroids and nitric oxide. In addition, studies have shown an upregulation of the angiotensin II type 2 receptor (AT2R) in aged females in comparison with males. Whilst incompletely understood, the AT2R is known to mediate vasodilation, nitric oxide release, and can be modulated by oestrogen. Work in this laboratory has shown that the expression of AT2R, renal ageing, and blood pressure may all be sensitive to the nutritional environment encountered during foetal development. This thesis aimed to elucidate some of the mechanisms mediating this ‘protective effect’ of female gender in a rat model of developmentally programmed hypertension and accelerated renal ageing. It was hypothesised that ageing would result in decreased renal function and increased blood pressure. These effects would be significantly altered by sex steroid modulation, and negative effects exacerbated by exposure to a low protein diet during gestation. The mechanisms driving these effects would be, at least in part, linked in changes to renin angiotensin system-regulated nitric oxide release. The data obtained suggested that the nitric oxide system did not significantly change with sex steroid exposure, or in response to maternal diet. Unexpectedly, ovariectomy alone did not change physiological responses as has been described previously. Instead, a significant interaction was observed between exposure to a low protein diet during gestation and ovariectomy. Offspring from mothers fed a low protein diet had impaired responses to removal of ovarian steroids. In addition, low protein offspring had altered vascular reactivity in response to targeted agonism and antagonism of angiotensin II receptors. In conclusion, this work has shown that the protective effect of female gender is more complex than previously described. The data did not support the hypothesis that nitric oxide mediates the beneficial effects of female sex, and targeted stimulation of the AT2R is not an effective means of altering this. Moreover, these data suggest that foetal exposure to a low protein diet may permanently programme altered vascular function, and can significantly affect response to sex steroids.